Detection of bla(CTX-M)-type genes in complex class 1 integrons carried by Enterobacteriaceae isolated from retail chicken meat in Brazil - Casella, Tiago [UNESP]; Rodriguez, Maria Margarita; Takahashi, Juliana Tiemi; Ghiglione, Barbara; Dropa, Milena; Assuncao, Ednei; Nogueira, Mauricio Lacerda; Lincopan, Nilton; Gutkind, Gabriel; Lelles Nogueira, Mara Correa (Elsevier B.V., 2015)
CIX-M-type extended-spectrum B-lactamase (ESBL)-producing Enterobacteriaceae have been increasingly identified in humans and animals, and their potential transmission by contaminated food has been highlighted. In this study, we report for the first time the isolation of multidrug-resistant (MDR) Escherichia coli, Klebsiella pneumoniae and Proteus mirabilis strains harboring bla(CTXM-2) or bla(CTXM-8) gene variants in chicken meat sold in markets in southeast Brazil. In this regard, the genetic environment of the bla(CTX-M-2) gene is composed of a complex class 1 integron and an ISCR1-associated sequence with dfr and/or aadA gene cassettes located within the variable region. In summary, chicken meat may be a reservoir of MDR Enterobacteriaceae harboring bla(CTX-M)-type genes, which is a public health concern. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Poultry; Chicken meat; CTX-M; ISCR1